A review on the prevalence and Detection of Bacterial contamination in Common Food and Associated Health Risk - Baidya, Sangita; Rahman, Tasmia (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.